2019
DOI: 10.1007/s00429-019-01957-y
|View full text |Cite
|
Sign up to set email alerts
|

Altered motor, anxiety-related and attentional task performance at baseline associate with multiple gene copies of the vesicular acetylcholine transporter and related protein overexpression in ChAT::Cre+ rats

Abstract: Transgenic rodents expressing Cre recombinase cell specifically are used for exploring mechanisms regulating behavior, including those mediated by cholinergic signaling. However, it was recently reported that transgenic mice overexpressing a bacterial artificial chromosome containing choline acetyltransferase (ChAT) gene, for synthesizing the neurotransmitter acetylcholine, present with multiple vesicular acetylcholine transporter (VAChT) gene copies, resulting in altered cholinergic tone and accompanying beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 137 publications
3
22
1
Order By: Relevance
“…While it is important to note that these effects could affect the conclusions drawn within the current study, we have recently compared the self-administration characteristics of wildtype Long Evans rats with ChAT::cre positive Long Evans rats and found no differences in total infusions across self-administration sessions or active and inactive lever pressing (Leyrer-Jackson, Overby et al 2020). Thus, while others have reported behavioral differences of ChAT::cre rats compared to wild type (Mantanona, Alsiö et al 2019), we believe that the lack of differences in self-administration characteristics demonstrate that these groups do not differ in their nicotine-seeking behaviors. However, future studies would benefit from comparing the MSN synaptic physiology and accumbens circuitry between ChAT::cre and wildtype rats.…”
Section: Limitations Of the Current Studymentioning
confidence: 68%
See 1 more Smart Citation
“…While it is important to note that these effects could affect the conclusions drawn within the current study, we have recently compared the self-administration characteristics of wildtype Long Evans rats with ChAT::cre positive Long Evans rats and found no differences in total infusions across self-administration sessions or active and inactive lever pressing (Leyrer-Jackson, Overby et al 2020). Thus, while others have reported behavioral differences of ChAT::cre rats compared to wild type (Mantanona, Alsiö et al 2019), we believe that the lack of differences in self-administration characteristics demonstrate that these groups do not differ in their nicotine-seeking behaviors. However, future studies would benefit from comparing the MSN synaptic physiology and accumbens circuitry between ChAT::cre and wildtype rats.…”
Section: Limitations Of the Current Studymentioning
confidence: 68%
“…Recent studies have demonstrated that ChAT::cre rats display elevated levels of the vesicular acetylcholine transporter protein, as well as altered motor, anxiety and attentional task performance (Mantanona, Alsiö et al 2019). While it is important to note that these effects could affect the conclusions drawn within the current study, we have recently compared the self-administration characteristics of wildtype Long Evans rats with ChAT::cre positive Long Evans rats and found no differences in total infusions across self-administration sessions or active and inactive lever pressing (Leyrer-Jackson, Overby et al 2020).…”
Section: Limitations Of the Current Studymentioning
confidence: 99%
“…The 5-CSRTT is a well-validated behavioural paradigm for assessing sustained spatial visual attention in rats ( Mantanona et al, 2019 ). The rats were trained and tested in Bussey-Saksida Touch Screen chambers (Lafayette Instrument, Indiana, USA) controlled by ABET II and Whisker control software ( Cardinal and Aitken, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…A standard touchscreen-based 5-CSRTT protocol was followed, as shown in Figure 1(a) and ( b ), and described previously ( Bharmal et al, 2015 ; Mantanona et al, 2019 ; Nilsson et al, 2016 ). Animals were trained to nose poke into a briefly illuminated, spatially random aperture.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, our approach of virally labeling cholinergic neurons in ChAT::Cre rats allows for cholinergic specificity, clear visualization of processes, and labeling of a large population of NBM cholinergic neurons. One caveat is that a recent publication found increased copies of the vesicular acetylcholine transporter gene in the prefrontal cortex of ChAT::Cre rats (41). It is not clear if this change would affect cholinergic dendritic morphology, but ChAT::Cre rats were used for both the control and VS conditions.…”
Section: Stress Induces Dendritic Hypertrophy In Nbm Cholinergic Neuronsmentioning
confidence: 99%